2020
DOI: 10.1038/s41562-020-00977-7
|View full text |Cite
|
Sign up to set email alerts
|

Partisan differences in physical distancing are linked to health outcomes during the COVID-19 pandemic

Abstract: Numerous polls suggest that COVID-19 is a profoundly partisan issue in the United States. Using the geotracking data of 15 million smartphones per day, we found that US counties that voted for Donald Trump (Republican) over Hillary Clinton (Democrat) in the 2016 presidential election exhibited 14% less physical distancing between March and May 2020. Partisanship was more strongly associated with physical distancing than numerous other factors, including counties' COVID-19 cases, population density, median inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
484
5
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 505 publications
(537 citation statements)
references
References 49 publications
46
484
5
2
Order By: Relevance
“…For institutional trust, the inconsistent and weak correlations between protective behaviour and institutional trust may be viewed as welcome news. According to the present data, political views and polarization does not necessarily jeopardize compliance in the outbreak of a massive global crisis like a pandemic, although it may naturally influence compliance at later stages (see Gollwitzer et al, 2020).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…For institutional trust, the inconsistent and weak correlations between protective behaviour and institutional trust may be viewed as welcome news. According to the present data, political views and polarization does not necessarily jeopardize compliance in the outbreak of a massive global crisis like a pandemic, although it may naturally influence compliance at later stages (see Gollwitzer et al, 2020).…”
Section: Discussionmentioning
confidence: 62%
“…Thus, in a democracy, compliance with public advice and policy is a function of citizen discretion, and, hence the authorities must rely on persuasion and voluntary compliance (Tyler & Jackson, 2014). Influence via communication requires an understanding of the psychology that this communication should tap into (Bonell et al 2020; Van Bavel et al 2020;West, Michie, Rubin, & Amlôt, 2020). For democratic governments' success in handling both the ongoing COVID-19 pandemic and potential future pandemics, it is key to understand the psychological correlates that motivated citizens to comply with public health advice in the initial drastic phase of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…13 Additionally, teachers unions, which have more power in blue states where mask-wearing and social distancing are more prevalent (Allcott et al, 2020;Katz et al, 2020), have opposed what they see as "reckless re-openings" and threatened strikes in response to planned re-openings (Cassella et al, 2020). physical distancing amidst the pandemic, and that political ideology matters more for the use of COVID mitigation strategies than other factors such as COVID rates and demographic characteristics (Adolph et al, 2020;Brenan, 2020;Clinton et al, 2020;Gollwitzer et al, 2020;Grossman et al, 2020;Schneider, 2020;Van Kessel & Quinn, 2020). Yet these same communities, on average, have higher rates of COVID-19 infection and death (Jones & Kiley, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the analyses supported what some nationwide studies have also claimed: higher income is associated with larger mobility reductions. Since preceding nationwide studies used aggregated location data to compare mobility across a nation (Dasgupta et al, 2020;Gollwitzer et al, 2020;Weill et al, 2020), it is noteworthy the disparity in mobility adaptation was observed among different income groups within a metropolitan statistical area where uniform executive orders were enforced.…”
Section: Indications Of the Findingsmentioning
confidence: 99%